Atmospheric-pressure particle mass spectrometer for investigating particle growth in spray flames. (November 2021) - Suleiman, Samer; Nanjaiah, Monika; Skenderovic, Ivan; Rosenberger, Thore; Kunze, Frederik; Wlokas, Irenaeus; Kruis, Frank Einar; Wiggers, Hartmut; Schulz, Christof
Abstract: In this work, we introduce a new particle mass spectrometer (AP-PMS) that is able to detect particle-size distributions at ambient pressure using a three-stage pumping design. This device is demonstrated for direct sampling from the particle formation in spray-flame synthesis of iron oxide nanoparticles. Aerosol sampling is performed by a probe with integrated dilution that has been characterized and configured by computational fluid dynamics simulations and the chamber-skimmer system has been investigated by schlieren imaging. The system was validated by detailed characterization of a standardized sooting flame and by iron oxide nanoparticles generated in the SpraySyn burner from iron nitrate dissolved in a mixture of ethanol and 2-ethylhexanoic acid. The PMS results are compared to additional inline measurements with SMPS and ELPI + as well as with TEM measurements of thermophoretically sampled materials from the same location in the spray flame. Highlights: New particle mass spectrometer detects particle-size distributions in spray flames. A three-stage pumping design allows particle sampling at ambient pressure. System validation by a standardized sooting flame and iron oxide nanoparticles.